2020
DOI: 10.1113/ep088550
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic right and left ventricular interactions in the pig

Abstract: I characterized the dynamic factors determining ventricular interdependence with and without the pericardium. I measured right (RV) and left ventricular (LV) pressures and volumes simultaneously using conductance catheters in seven pentobarbitoneanaesthetized open-chested 5-to 7-week-old piglets. I studied these effects during apnoea, inferior vena caval occlusion and rapid partial aortic and pulmonary arterial occlusions. Conductance catheter-defined long-axis regional volumes were assessed to define regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
(95 reference statements)
4
4
0
Order By: Relevance
“…36 The importance of an external constrain for the transseptal pressure gradient is discussed elsewhere. 37,38 Pinsky 38 showed that increased right ventricular systolic pressure did not affect systolic ventricular interdependence, supporting our observations of unaltered left ventricular ejection fraction and end-systolic pressure-volume relationship.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…36 The importance of an external constrain for the transseptal pressure gradient is discussed elsewhere. 37,38 Pinsky 38 showed that increased right ventricular systolic pressure did not affect systolic ventricular interdependence, supporting our observations of unaltered left ventricular ejection fraction and end-systolic pressure-volume relationship.…”
Section: Discussionsupporting
confidence: 83%
“…The transseptal pressure gradient also decreased. This may affect diastolic ventricular interdependence, 38 and may be a part of the explanation of our observations on tau for both ventricles concomitant with the reduced end-diastolic volume and end-diastolic pressure, especially for the right ventricle.…”
Section: Discussionmentioning
confidence: 79%
“…Pericardiotomy trended to cause LV dilatation, as shown significantly previously (Angelini et al, 1990) on the pre-interventional situation, which confirms previous findings (Pinsky, 2020). Likewise, interventricular dependence has been shown…”
Section: Ventricular Functionssupporting
confidence: 89%
“…The physiological effects of cardiac constraint by the pericardium, lungs and chest wall and how the removal of an external constraint will reduce the impact of any intervention of interest have been discussed for decades (Belenkie et al., 2004 ; Butler, 1983 ; Lloyd, 1982 ; Pinsky, 2020 ; Pinsky et al., 1983 ), supporting our aim of quantifying the changes on modern cardiovascular equipment in order to improve rigorous reporting. Furthermore, we emphasize the importance of researchers choosing a clinically relevant animal model (open vs. closed chest) mimicking their field of interest, but we cannot provide a single best model for specific cardiac disease paradigms.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation